Космический эксперимент «Трубка»: автоматизированное управление и система измерений температуры - Косторнов, А.Г.; Сурду, М.Н.; Фролов, Г.А.; Ламеко, А.Л.; Шаповал, А.А.; Еланский, Ю.А.; Тихий, В.Г.; Гусарова, И.А.; Шаповал, И.В. (Проблемы управления и информатики, 2008)
Розглянуто стан робіт з підготовки наукової апаратури для проведення космічного експерименту «Трубка», зокрема системи автоматизованого керування експериментом та точного вимірювання температури дослідних теплових труб. Отримані результати дозволять успішно виконати завдання експерименту на борту російського сегмента МКС. Questions of development of the scientific equipment for realization of space experiment «Trubka» are considered. The system of automated control of experiment and system of exact measurements of temperature of pilot heat pipes is created and tested. Scientific results received while creation of system of automated control and temperature measurement are presented. These results will allow to solve problems of space experiment which will be carried out on board of the international space station.